Impacts of a railway tunnel on the streams baseflow verified by means of numerical modelling - Piccinini, Leonardo; Vincenzi, Valentina (Acque Sotterranee - Italian Journal of Groundwater, 2021)
The high-speed railway line between Bologna and Florence (Italy) is mostly developed underground through the Tuscan-Emilian Apennine, and the tunnels severely impacted groundwater and surface water. The 15-km-long Firenzuola tunnel crosses siliciclastic turbidites: during drilling, water inrushes occurred at fault and fracture zones, and the tunnel continues to drain the aquifer. The water table dropped below the level of the valleys, and gaining streams transformed into losing streams or ran completely dry, as did many springs. Hydrological observations and two multitracer tests have previously characterized the stream-tunnel connections and the impact processes. In the framework of planning mitigation strategies to minimize impacts on stream baseflow, three-dimensional numerical modelling with MODFLOW (the EPM approach) is applied to evaluate the artificial minimum flow needed to maintain flow continuity along the stream during the recession phase. The establishment of the two presented models is based on hydrogeological monitoring data and the results of flow measurements and tracer tests. Maximum flow rates subtracted from stream baseflow by the tunnel along the connection structures are calculated for two streams with major impacts.